Positive Economic Impacts: An Analysis of Tourism in Panama Region - Nisthar, S.; Vijayakumar, S.; Nufile, A.A.M. (Faculty of Arts and Culture, South Eastern University, 2021)
The main objective of this study is to examine the determinants of the positive economic impacts of tourism sector and their relationship with the total impacts on the local community in Panama region of Sri Lanka by using quantitative approach. Arugambay, Kottukal, Jalaldeen Square, Kudakalliya, and Panama are the touristic destinations selected in the Panama Region of Sri Lanka. In the quantitative approach, the questionnaire with five-Likert scale format is used to collect the primary data in 2017/2018. The selected sample size is 530 which represent of hoteliers, employees, and community members. Multicollinearity Analysis, Multiple Regression Analysis, and Residual Analysis are the econometric techniques used to analyze the data by employing SPSS v.20 software. The factors such as Savings & Investment, Payment for Labour, Employment, Earnings of Business are the independent variables. The most important independent variables are Payment for Labour and Earnings of Business. The regression analysis assures and vividly confirms the significant effects of the positive economic factors.
Keywords: Negative impacts; Total effect; Factor analysis; Panama region; Multiple regression